A new approach to distance measurements between two spin labels in the >10 nm range - Blank, A (Physical chemistry chemical physics : PCCP, 2017)
ESR spectroscopy can be efficiently used to acquire the distance between two spin labels placed on a macromolecule by measuring their mutual dipolar interaction frequency, as long as the distance is not greater than ∼10 nm. Any hope to significantly increase this figure is hampered by the fact that all available spin labels have a phase memory time ( T m ), restricted to the microseconds range, which provides a limited window during which the dipolar interaction frequency can be measured. Thus, due to the inverse cubic dependence of the dipolar frequency over the labels' separation distance, evaluating much larger distances, e.g. 20 nm, would require to have a T m that is ∼200 microsecond, clearly beyond any hope. Here we propose a new approach to greatly enhancing the maximum measured distance available by relying on another type of dipole interaction-mediated mechanism called spin diffusion. This mechanism operates and can be evaluated during the spin lattice relaxation time, T 1 (commonly in the milliseconds range), rather than only during T m . Up until recently, the observation of spin diffusion in solid electron spin systems was considered experimentally impractical. However, recent developments have enabled its direct measurement by means of high sensitivity pulsed ESR that employs intense short magnetic field gradients, thus opening the door to the subsequent utilization of these capabilities. The manuscript presents the subject of spin diffusion, the ways it can be directly measured, and a theoretical discussion on how intramolecular spin-pair distance, even in the range of 20-30 nm, could be accurately extracted from spin diffusion measurements. ESR spectroscopy can be efficiently used to acquire the distance between two spin labels placed on a macromolecule by measuring their mutual dipolar interaction frequency, as long as the distance is not greater than ∼10 nm.